Exact Formulas for E^θ/G/1/N-Type Queuing Systems - Bratiichuk, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate E θ/G/1/N-type queuing systems with limited queue. The investigation is based on the potential method proposed by Korolyuk